Improvement of Permit to Work Process to Enhance Performance of Business Partner in PT XYZ - Sudarmo, Yogie Rahedian; Wiyana, Aldo Fantinus (The Indonesian Journal of Business Administration, 2013)
Operation and Maintenance (O&M) division as one of division in PT XYZ was chosen for efficiency project implementation. Since, it spends 35% of budget. O&M is faced by low performance of business partner. It is seen from time writing (TW) utilization and overtime ratio that are below standard. TW utilization is 61,7% and overtime ratio is 36%. And for this PT XYZ should spend cost of poor quality about USD 170.000 per annum.Excessive procedural of permit to work (PTW) has been found as one of the causes. Lead time of PTW will take 28 hours with execution time 3 hours and 30 minutes. With new proposed PTW process, lead time of PTW will take 27 hours with execution time 5 hours and 30 minutes. And it has resulted to new proposed contract for business partner where it will start work at 08.00 AM. Potential benefit is as much as USD 143.596 per annum. Keywords: Process Improvement, Excessicive Procedural, Cost of Poor Quality, Permit to Work, Contract